Fostering sustainable development values among engineering students using Service-Learning - López-Santiago, Jesús; de Francisco Alonso, Mónica; Zubelzu-Minguez, Sergio; Ruiz-Garcia, Luis; Gómez-Villarino, María Teresa (Frontiers in Education, 2024)
In the majority of nations, environmental sustainability is an integral aspect of government policies, highlighting the criticality of equipping upcoming engineers with the necessary environmental awareness and skills to tackle this complex challenge. Higher education institutions assume a pivotal role in fulfilling this mission as their engineering programs aspire to generate graduates who possess the necessary competencies to effectively operate as “sustainable” engineers. Novel pedagogical methodologies, such as service learning, are currently being utilized to foster the cultivation of sustainable development values. Service-Learning represents a highly congruent approach to achieving Sustainable Development Goal (SDG) 4, insofar as it seamlessly integrates educational curricula with relevant community issues. As a result, it effectively contributes to the advancement of education for a sustainable future. This investigation sought to assess the impact of service learning projects developed in a rural school community on the boosting of social skills and environmental values among engineering students. The empirical evidence suggests that Service-Learning initiatives centered on environmental issues are efficacious in promoting the acquisition of social and environmental values among students. This, in turn, results in a positive transformation of their skill sets. Significantly, a substantial proportion of environmental engineering students who previously demonstrated a low awareness of these skills acknowledged their acquisition upon completion of the Service-Learning projects. Moreover, no less than 75% of the participants endorsed the attainment of each of the 11 competencies evaluated.